Step-by-step Solution

Solve the differential equation $\left(4y+yx^2\right)dy-\left(2x+xy^2\right)dx=0$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Step-by-step explanation

Problem to solve:

$\left(4y+yx^2\right)dy-\left(2x+xy^2\right)dx=0$

Learn how to solve differential equations problems step by step online.

$\left(4y+yx^2\right)dy=\left(2x+xy^2\right)dx$

Unlock this full step-by-step solution!

Learn how to solve differential equations problems step by step online. Solve the differential equation (4y+yx^2)dy-(2x+xy^2)*dx=0. Grouping the terms of the differential equation. Grouping all terms to the left side of the equation. Solve the product \left(4y+yx^2\right)dy. Solve the product -\left(2x+xy^2\right)dx.

Final Answer

$y=\frac{4}{x}+C_0$

Problem Analysis